Adaptive governance strategies to address wildfire and watershed resilience in New Mexico's upper Rio Grande watershed - Morgan, Melinda; Webster, Alex; Piccarello, Matt; Jones, Kelly; Chermak, Janie; McCarthy, Laura; Srinivasan, Jaishri (Frontiers in Climate, 2023)
Global climate models project that New Mexico’s Upper Rio Grande watershed is expected to become more arid and experience greater climatic and hydrological extremes in the next 50 years. The resulting transitions will have dramatic implications for downstream water users. The Upper Rio Grande and its tributaries provide water to about half of New Mexico’s population, including the downstream communities of Albuquerque and Santa Fe, and surrounding agricultural areas. In the absence of formal climate adaptation strategies, informal governance arrangements are emerging to facilitate watershed climate adaptation strategies, including fuel treatments and stream remediation. One example is the Rio Grande Water Fund (RGWF), a collaborative effort coordinating work to protect storage, delivery, and quality of Rio Grande water through landscape-scale forest restoration treatments in tributary forested watersheds. This article examines the RGWF as one example of an emerging adaptation strategy that is working within—and beyond—existing legal and policy frameworks to accomplish more collaborative efforts across jurisdictional lines and administrative barriers. We identified ten (10) key characteristics of adaptive governance from the relevant literature and then applied them to the RGWF’s experience in the watershed to date. Key findings include: (1) the RGWF’s approach as a collaborative network created the right level of formality while also keeping flexibility in its design, (2) a scalar fit to the environmental challenge built social capital and investment in its work, (3) leadership from key stakeholders leveraged opportunities in the watershed to create and maintain stability, and (4) use of adaptive management and peer review processes built capacity by creating the feedback loops necessary to inform future work.